2023
DOI: 10.1021/acs.jpcb.2c08077
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cholesterol on the Membrane Binding and Conformation of α-Synuclein

Abstract: The α-Synuclein (α-Syn) plays an important role in the pathology of Parkinson’s disease (PD), and its oligomers and fibrils are toxic to the nervous system. As organisms age, the cholesterol content in biological membranes increases, which is a potential cause of PD. Cholesterol may affect the membrane binding of α-Syn and its abnormal aggregation, but the mechanism remains unclear. Here, we present our molecular dynamics simulation studies on the interaction between α-Syn and lipid membranes, with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Interestingly, the association constants for the current lipid-coated gold nanoparticle mimics are roughly 1–2 orders of magnitude higher than those of previously studied sodium dodecyl sulfate coated gold nanoparticles and citrate-capped gold nanoparticles analyzed by the same approach (Table ). This increased affinity could be a result of packing defects and grain boundaries arising in the more complex, mixed lipid surface chemistry, as previous studies have suggested that alpha-synuclein exhibits heightened affinity for such defects in lipid bilayers. ,, However, factors such as ionic strength, pH, and temperature can also impact protein binding affinities and should be considered as a point of caution when comparing results across multiple studies conducted under different experimental conditions, even when the same method of analysis was applied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the association constants for the current lipid-coated gold nanoparticle mimics are roughly 1–2 orders of magnitude higher than those of previously studied sodium dodecyl sulfate coated gold nanoparticles and citrate-capped gold nanoparticles analyzed by the same approach (Table ). This increased affinity could be a result of packing defects and grain boundaries arising in the more complex, mixed lipid surface chemistry, as previous studies have suggested that alpha-synuclein exhibits heightened affinity for such defects in lipid bilayers. ,, However, factors such as ionic strength, pH, and temperature can also impact protein binding affinities and should be considered as a point of caution when comparing results across multiple studies conducted under different experimental conditions, even when the same method of analysis was applied.…”
Section: Resultsmentioning
confidence: 99%
“…This increased affinity could be a result of packing defects and grain boundaries arising in the more complex, mixed lipid surface chemistry, as previous studies have suggested that alpha-synuclein exhibits heightened affinity for such defects in lipid bilayers. 22,44,45 However, factors such as ionic strength, pH, and temperature can also impact protein binding affinities 46−48 and should be considered as a point of caution when comparing results across multiple studies conducted under different experimental conditions, even when the same method of analysis was applied.…”
Section: Synthesis and Characterization Of Biologically Representativ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent ndings indicate that Lewy bodies in addition of the high level of alpha-syn proteins are also characterized by a high lipid content and degenerated organelles suggesting that lipids, which are the main constituents of cell membranes, may contribute to the development of the disease (Shahmoradian et al, 2019;Mahul-Mellier et al, 2020). Over the last two decades, accumulating evidence suggests a transient binding of alpha-syn to lipid membranes particularly in cholesterol-rich regions (Fortin et al, 2004;van Maarschalkerweerd et al, 2015;Kachappilly et al, 2022;Qi et al, 2023). Cholesterol may affect the binding of alpha-syn to the membrane and its abnormal aggregation (Man et al, 2020;Jakubec et al, 2021;Qi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, accumulating evidence suggests a transient binding of alpha-syn to lipid membranes particularly in cholesterol-rich regions (Fortin et al, 2004;van Maarschalkerweerd et al, 2015;Kachappilly et al, 2022;Qi et al, 2023). Cholesterol may affect the binding of alpha-syn to the membrane and its abnormal aggregation (Man et al, 2020;Jakubec et al, 2021;Qi et al, 2023). Studies have also demonstrated that alpha-syn signi cantly stimulates cholesterol e ux (Hsiao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%